1994
DOI: 10.1046/j.1471-4159.1994.63041529.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Translocation of Cytosolic Ca2+/Calmodulin‐Dependent Protein Kinase II into Postsynaptic Density After Decapitation

Abstract: The postsynaptic density (PSD) fraction prepared from rat forebrains frozen with liquid nitrogen immediately after dissection (within 30 s after decapitation) contained major postsynaptic density protein (mPSDp), a subunit of Ca2+/calmodulin-dependent protein kinase II (CaMKII) at a level of merely 2.7% of the total protein. The content ofthe protein in the fraction was increased to --10% by placing the forebrains on ice for a few minutes . Accumulation, but to a lesser extent, of the protein after placement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 25 publications
5
82
0
Order By: Relevance
“…Because of this, we assume that the αCaMKII in our TxP fraction represented predominantly PSD-associated kinase. The TxP fraction contained the highest relative concentration of αCaMKII, indicating that, as expected based on previous results (Kennedy et al, 1983;Petersen et al, 2003;Suzuki et al, 1994), αCaMKII is enriched at the post-synaptic density in recovered CA1-minislices from adult rats.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Because of this, we assume that the αCaMKII in our TxP fraction represented predominantly PSD-associated kinase. The TxP fraction contained the highest relative concentration of αCaMKII, indicating that, as expected based on previous results (Kennedy et al, 1983;Petersen et al, 2003;Suzuki et al, 1994), αCaMKII is enriched at the post-synaptic density in recovered CA1-minislices from adult rats.…”
Section: Resultssupporting
confidence: 88%
“…Previous studies have demonstrated that the conditions encountered during sacrifice and hippocampal slice preparation lead to alterations in T286 phosphorylation (Lengyel et al, 2001;Ho et al, 2004), an increase in CaMKII concentration in PSD-enriched fractions (Suzuki et al, 1994), and CaMKII cluster formation (Dosemeci et al, 2000;Tao-Cheng et al, 2002). Because of this, all of the CA1-minislices used in this study were allowed to recover for at least 90 minutes following sacrifice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, under the pathological conditions, such as cerebral ischemia, over-stimulation of the neurotransmitter receptors may cause extensive oxidation of CaMKII. Thus, a combination of oxidation with intracellular acidification under these conditions (51) could account for the severe inactivation of the kinase and accumulation of both the synaptic and non-synaptic CaMKII aggregates (11,12,40,(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%